Safety requirements for cableway installations designed to carry persons - Terminology (BSI, 2005)
Passenger ropeways, Aerial ropeways, Passenger transport, Aerial equipment, Materials handling equipment, Terminology, Design, Maintenance, Definitions, Vocabulary